Synthesis, 5-Hydroxytryptamine1a Receptor Affinity and Docking Studies of 3-[3-(4-Aryl-1-Piperazinyl)-Propyl]-1h-Indole Derivatives - Reyes-Parada, M (Pharmaceutical Society of Japan, 2012)
A series of 3-[3-(4-aryl-1-piperazinyl)-propyl]-1H-indole derivatives (12a-h) was synthesized and evaluated for binding affinity at the human 5-hydroxytryptamine1A receptor (5-HT1AR) compounds (12b) and (12h) showed the highest 5-HT1A receptor affinity (IC 50-=15 nM). Molecular docking studies with all the compounds in a homology model of 5-HT1A showed that the main interaction anchoring the ligand in the receptor was a charge-reinforced bond between the protonated nitrogen atom (N-4) of the piperazine ring and Aspartate3.32. © 2012 The Pharmaceutical Society of Japan.